2020
DOI: 10.3390/en13040933
|View full text |Cite
|
Sign up to set email alerts
|

Two Phase Anaerobic Digestion System of Municipal Solid Waste by Utilizing Microaeration and Granular Activated Carbon

Abstract: In an anaerobic digestion (AD) process, the hydrolysis phase is often limited when substrates with high concentrations of solids are used. We hypothesized that applying micro-aeration in the hydrolysis phase and the application of granular activated carbon (GAC) in the methanogenesis phase could make the AD process more efficient. A packed bed reactor (PBR) coupled with an up-flow anaerobic sludge blanket (UASB) was conducted, and its effects on methane generation were evaluated. The micro-aeration rate applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Analyzing the data for each evaluated aspect, it was observed that volatile fatty acids (VFA) observed an increasing behavior, alkalinity gradually decreased, pH decreased, and methane concentration stabilized within a range of 60% to 70% (Figure 3). These behaviors were similar to those reported by [26,35] in the stabilization of the UASB reactor, which allows for establishing the starting point to start joining the process of hydrolysis and methanogenesis.…”
Section: Characterization Of Citrus Residuessupporting
confidence: 85%
See 1 more Smart Citation
“…Analyzing the data for each evaluated aspect, it was observed that volatile fatty acids (VFA) observed an increasing behavior, alkalinity gradually decreased, pH decreased, and methane concentration stabilized within a range of 60% to 70% (Figure 3). These behaviors were similar to those reported by [26,35] in the stabilization of the UASB reactor, which allows for establishing the starting point to start joining the process of hydrolysis and methanogenesis.…”
Section: Characterization Of Citrus Residuessupporting
confidence: 85%
“…The behavior of the data at the beginning of the hydrolysis and acidogenesis stage, until the union of the two reactors, was favorable to what was reported in the literature according to [35], who managed to define homogeneous and reproducible behavior, with variables such as pH, VFA, biogas concentration and COD for both reactors. In Figure 6a, the specific behavior of the pH before and after the union of the reactors is shown, evidencing a semi-constant behavior before starting the union of the two systems, where it can be evidenced that the coupling of the systems did not affect the pH of the UASB reactor and remained in the same range.…”
Section: Coupled Systemsupporting
confidence: 78%
“…Sparging oxygen into the system causes an increase in the ORP values. For instance, ORP values ranging from −215 to −150 mV are normal for reactors subjected to microaeration [45]. Some authors have pointed out the importance of ORP intervals on gene expression, protein biosynthesis, and control strategies for more efficient production of byproducts [39].…”
Section: Indirect Measurement Techniquesmentioning
confidence: 99%
“…A two-phase digestion system for the treatment of municipal solid waste, involving micro-aeration and GAC added as a supplement, was evaluated by Canul Bacab et al [174], demonstrating the feasibility of this approach for attaining fast hydrolysis, reducing digestion time, and enhancing methane production. An initial aerobic phase, prior to digestion, was proposed as a pre-treatment to increase the hydrolysis of lignocellulosic material [175].…”
Section: Temperature and Digestion Performancementioning
confidence: 99%